(untitled) (Applied Biological Research, 2012)
Pebrine is a deadly disease of silkworm causing serious damage in silkworm and is directly responsible for the decline of sericulture industry in many countries. The disease is caused by Nosema ricini, a pathogenic microsporidian (Microsporidia: Nosematidae) in eri silkworm, Philosamia ricini Boisd. This paper for the first time documents a detailed study on morphology and life cycle stages of N. ricini as observed under light, scanning and transmission electron microscopy. The mature spores of N. ricini were elliptical in shape, blunt or tapering at both ends and small in length (3.80.06 µm), breadth (2.60.03 µm) and volume (13.7 µm3). Mature spore had hard spore wall and slight concavity or were tapered at both the ends of spore with smooth external morphology as seen under SEM. The main components of spore viz., sporoplasm, polar filament, polar cap, anterior and posterior vacuole, and spore shell were observed in TEM study. The polar filament ran oblique course backward from its base at the centre of the polar sac, narrowed slightly in diameter gradually upto the end and formed a coil in peripheral layer of cytoplasm. The number of coils was 10-12. Life cycle includes two distinct stages, spore and vegetative. N. ricini was found highly species specific.